Pemberdayaan UMKM sebagai Solusi Produk Inovasi Pemanfaatan Limbah Kulit Pisang dan Arang Kayu sebagai Produk Semir Sepatu di Desa Seren - Nur Jihad Demokrasiyanto; Fitri Nurul Fatimah; Ahmad Fawwazun Rifqi; Marfuah Marfuah; Wildan Adib Furqon; Arini Lutfi Solihah; Rizki Adi Nugroho; Airlangga Bagus Pratama Putra Subandi; Fazira Andra Putri; Panca Wisnu Wardani; Muhammad Danial Fitroh; Safira Azkiya Putri; Rahma Dhara Zafira; Alfin Muzakki Thoha; Nukhbatun Nisa; Hidayatus Sibyan (Pusat Riset dan Inovasi Nasional, 2026)
Seren Village has abundant organic waste potential, particularly banana peel waste generated from banana-processing MSME activities and wood ash resulting from household firewood combustion. To date, this waste has not been optimally utilized and is often discarded, thereby posing potential environmental problems. This study aims to process banana peel waste and wood ash into an innovative, environmentally friendly shoe polish made from natural materials, while also enhancing the economic value and welfare of the community. The research employed a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and documentation involving the women’s Family Welfare Empowerment Group (PKK) of Seren Village as the target participants. The shoe polish production process includes drying and grinding banana peels, mixing them with a wood ash solution that functions as a natural coloring agent, adding supporting materials, and heating the mixture until a ready-to-use shoe polish is obtained. The results indicate that the shoe polish produced from banana peels and wood ash has a solid texture, is slightly coarse, non-glossy, and has a relatively fast drying time of approximately one minute. In addition, the product shows good resistance to water splashes and does not damage the surface of shoes. The use of natural ingredients makes this shoe polish safer for health. The utilization of this waste has the potential to support MSME development, reduce environmental pollution, and sustainably improve the welfare of the Seren Village community.